Awareness and knowledge of oral cancer among final year undergraduate dental students in Baghdad-Iraq - Diajil, Ameena R (Journal of Baghdad College of Dentistry, 2013)
Background: The incidence of oral cancers is increasing all over the world. Early detection ofthis important public health matter makes them more amenable to treatment and allows the greatest chance of cure.The aim of this study was to investigate the awareness and knowledge on oral cancer among final -year dental students in Iraq.Materials and methods: Questionnaires were delivered to 160 final–year dental students in the College of Dentistry in Baghdad. The questionnaire focused on the awareness/knowledge of oral cancer, earlyand common clinical signs and symptoms andassociated risk factors. Results: It was found that 87% of students were aware of oral cancer. The followings were recognized as signs and symptoms of oral cancer: persistent ulcer and lymphadenopathy (71 %, 70%), followed by presence of white patch (63%). A satisfactory knowledge was observed on; smoking (86%), family history (84%), old age (63%), sun light exposure (59%), smokeless tobacco (57%), alcohol consumption (55%) and Immunosuppression (54%).Considering dilatory risk-factors, a satisfactory knowledge was identified on hot and spicy food (57%), but not on the other factors. Although satisfactory knowledge of dental risk-factors including premalignant disorders (84%) and previous history of oral cancer (70%) was observed, inadequate knowledge about other factors was observed.91% of future dentists indicated that oral cancer can be cured when detected early.Conclusion: This study highlighted the need for more education in dental schools to enhance dental professionals’ awareness and knowledge of oral cancer, aiding in early diagnosis and treatment of patients.